Sources and Components of Stigma Experienced by Survivors of Intimate Partner Violence. - Murray, Christine E; Crowe, Allison; Overstreet, Nicole M (Journal of interpersonal violence, 2015)
Previous research suggests that survivors of intimate partner violence (IPV) experience stigma, which may affect their willingness to seek help and their recovery process following the end of the abusive relationship. This article presents the Integrated IPV Stigmatization Model, which integrates previous research on the components and sources of the stigma surrounding IPV. Content analysis procedures were used to examine the applicability of the model to qualitative data from an electronic survey with 279 survivors of past abusive relationships. The results demonstrated the most common components and sources of stigma experienced by the participants, as well as the patterns of which components were most common among the various sources of stigma. Implications for future research and clinical practice are discussed.